Complaints of group-stalking (‘gang-stalking’): an exploratory study of their nature and impact on complainants - Sheridan, Lorraine; James, D. (Routledge, 2015)
© 2015 Taylor & Francis. Stalking primarily concerns the actions of individuals. However, some victims report stalking by organised groups, this being known as ‘group-’ or ‘gang-stalking’. This phenomenon has not been subject to systematic study. An anonymous questionnaire was completed online by self-defined victims of stalking. One thousand and forty respondents met research definitions for stalking, of which 128 (12.3%) reported group-stalking. One hundred and twenty-eight individually stalked cases were randomly selected as a comparison group. All cases of reported group-stalking were found likely to be delusional, compared with 3.9% of individually stalked cases. There were highly significant differences between the two groups on most parameters examined. The group-stalked scored more highly on depressive symptoms, post-traumatic symptomatology and adverse impact on social and occupational functioning. Group-stalking appears to be delusional in basis, but complainants suffer marked psychological and practical sequelae. This is important in assessment of risk in stalking cases, early referral to psychiatric services and allocation of police resources.